2023
DOI: 10.1088/1361-6439/acef32
|View full text |Cite
|
Sign up to set email alerts
|

A novel micro-device for simultaneous separation-trapping and double-trapping of particles by using dielectrophoresis: numerical and experimental study

M Aghdasi,
M Nazari,
Sareh Yonesi

Abstract: Dielectrophoretic (DEP) force is a useful tool for manipulating particles in microfluidic systems. It is affected by the frequency of the applied electric field, which can be varied to produce repellent and attractive forces depending on the dielectric properties of particles and the media. In this work, two electric fields with different frequency are used to simultaneously separate and trap particles as well as double-trap particles by utilizing the DEP force. Initially, a single-vial microchannel was propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…However, it is observed that the electrolyte temperature was neglected and, to the author's knowledge, no FEM study has been performed to analyze the productivity and accuracy of the ECDM process based on the electrolyte temperature. In the literature [29], a simulation study along with experimentation was conducted to comprehend the mechanism of novel microdevices.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is observed that the electrolyte temperature was neglected and, to the author's knowledge, no FEM study has been performed to analyze the productivity and accuracy of the ECDM process based on the electrolyte temperature. In the literature [29], a simulation study along with experimentation was conducted to comprehend the mechanism of novel microdevices.…”
Section: Introductionmentioning
confidence: 99%